2018
DOI: 10.1080/21645515.2018.1457595
|View full text |Cite
|
Sign up to set email alerts
|

Four-year antibody persistence and response to a booster dose of a pentavalent MenABCWY vaccine administered to healthy adolescents and young adults

Abstract: This open-label, multicenter extension study (NCT02451514) assessed persistence of Neisseria meningitidis serogroups ABCWY antibodies 4 years after primary vaccination. Adolescents and young adults who previously received 2 doses of MenABCWY+OMV (Group III), 1 dose of MenACWY-CRM (Group VI), or newly-recruited vaccine-naïve participants (Group VII) were administered 1 (Group III) or 2 doses (Groups VI and VII) of MenABCWY+OMV, 1 month apart. Immunogenicity was assessed by human serum bactericidal assay (hSBA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…Investigation of a next-generation, pentavalent combination MenABCWY-CRM-conjugated vaccine has been started in adolescents and adults [ 105 , 106 , 107 , 108 , 109 , 110 ]. This vaccine combines MenACWY-CRM and the 4CMenB vaccine and has been developed to provide broader protection against the five most epidemiologically relevant serogroups.…”
Section: Meningococcal Protein-based Vaccinesmentioning
confidence: 99%
“…Investigation of a next-generation, pentavalent combination MenABCWY-CRM-conjugated vaccine has been started in adolescents and adults [ 105 , 106 , 107 , 108 , 109 , 110 ]. This vaccine combines MenACWY-CRM and the 4CMenB vaccine and has been developed to provide broader protection against the five most epidemiologically relevant serogroups.…”
Section: Meningococcal Protein-based Vaccinesmentioning
confidence: 99%
“…As MenB and MenACWY vaccines cover most disease-causing serogroups [5], guidelines that include concomitant administration of these two vaccines can help protect against the majority of meningococcal disease worldwide and would likely improve compliance by requiring fewer medical visits [172][173][174]. Alternatively, a single pentavalent MenABCWY vaccine, currently in development [175,176], could potentially simplify existing meningococcal vaccine recommendations and increase the convenience of vaccination to optimize the protection of those at risk [32,177].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study from New Zealand examined whether MenB vaccination could be protective against diseases caused by other Neisseria species and found that individuals immunized with an OMV MenB vaccine were significantly less likely to be hospitalized due to N gonorrhoeae infection [107]. In addition, as noted above, pentavalent MenABCWY vaccines are currently in development, which should simultaneously protect individuals against the five common disease-causing serogroups [175,176]. Both MenB-4C and MenB-FHbp contain FHbp, which is found in most IMD strains across serogroups [15,16,91].…”
Section: Expert Opinionmentioning
confidence: 99%
“…MenA, W, and Y hSBA titers ≥4 were ≥41% (95% [CI]: [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] and ≥37% (95% CI 24-51) in the MenACWY-TT and MenC-CRM 197 groups, respectively. One-month post-booster with the ACWY-TT vaccine, rSBA GMT against the four serogroups increased ≥42-fold.…”
Section: Meningococcal Vaccine Responses Measured By Rsba and Hsba Inmentioning
confidence: 99%
“…Antibody persistence has been demonstrated following the currently licensed meningococcal ACWY conjugate vaccines though new quadrivalent vaccines that are undergoing development will be licensed in the future [48]. A further development is likely to see new meningococcal vaccines where the serogroup B protein-based vaccines are incorporated into the quadrivalent ACWY conjugates yielding pentavalent ABCWY vaccines [49].…”
Section: Five Year Viewmentioning
confidence: 99%